Effect of Zinc Supplementation on Duration of Hospital Stay in Childhood Pneumonia - Ahmed, ATM Faruque; Hyder, Rumy Tabrez; Sufian, Abu; Hossain, Abir; Majumder, Ripon Chundra (Eastern Medical College Journal, 2022)
Background: Pneumonia is one of the major causes of death in children younger than age five, especially in developing countries. Supplementation with zinc is effective in the treatment and prevention of childhood pneumonia. Objective: To assess the duration of hospitalization after zinc supplementation in childhood pneumonia. Materials and Methods: This randomized double blind controlled trial was conducted in the Department of Pediatrics, Sylhet MAG Osmani Medical College Hospital, Sylhet during the period from 1st July 2013 to 30th June 2015. A total of 120 patients with severe pneumonia in hospitalized children fulfilling inclusion and exclusion criteria were enrolled by systematic random sampling. Group allocation of Group-A and Group-B was done by lottery method each consisting of 60 and 60 patients. Identically small packets that contained 10mg zinc sulphate powder or 10 mg placebo powder were coded as A and B by guide. Results: Time for normalization of all parameters (clinical recovery) in placebo group and zinc group was 127.12±24.58 hours and 111.23±35.47 hours respectively which were statistically significant (p<0.05). All patients of both groups were discharged. The mean duration of hospital stay was found to be 6.78±0.42 days in placebo group and 5.42±0.81 days in zinc group. Mean duration of hospital stay was significantly less in zinc group in comparison to placebo (p<0.05). Conclusion: Supplementation of zinc therapy in childhood pneumonia causes early clinical recovery and less duration of hospital stay in comparison to the non-zinc therapy group. Eastern Med Coll J. Jan 2023; 8 (1) 15-18